Imami Shiite scholars in the Islamic East in the fifth century AH and their most prominent scientific and intellectual production - م.م. وسام رعد سلوم; م. د. سيد محمد حسيني; أ. د. ثامر نعمان مصطاف (Journal of College of Education, 2023)
The study aims to demonstrate the impact of the Imami Shiite scholars in the Islamic East, to answer the suspicions of the Imami Shiite thought, as it was dominated by stagnation in intellectual and scientific achievement, as the fifth century witnessed the fall of the Buyid rule and the Seljuk state, which was characterized by violence, especially with the Shiites, and their oppression against the Shiites reached to A degree that no one dares to, as they cannot declare their doctrine, and many works appeared that were targeting the Ahl al-Bayt (PBUH), which prompted Shiite scholars to rush to defend the doctrine of Shiites in front of umbrella ideas, so they spread science in all fields of knowledge, and the Shiites responded to many books against Their opponents, where some Shiite cities were looted, including the city of Qom and the city of Kashan, as well as the city of Rawand.
Keywords: Imamate Shiites, Seljuks, the Islamic East, the fifth century AH.